Science as power : discourse and ideology in modern society - Aronowitz, Stanley (University of Minnesota Press, 1988)
Science has established itself as not merely the dominant but the only legitimate form of human knowledge. By tying its truth claims to methodology, science has claimed independence from the influence of social and historical conditions. Here, Aronowitz asserts that the norms of science are by no means self-evident and that science is best seen as a socially constructed discourse that legitimates its power by presenting itself as truth.